Transformação digital e mudanças no formato de trabalho: Impactos na estrutura organizacional de instituições bancárias brasileiras - Constantino, Rafael Henrique (2023)
In a world in constant technological transformation, in which consumer expectations and demands are increasingly greater, with a constant entry of new competitors in the highly competitive and dynamic market, organizational efforts with well-defined strategies and that are able to adapt quickly to new conditions. Choosing the path of digital transformation and creating the possibility for your professionals to work in locations other than the company's headquarters are trends that have been gradually implemented as organizational strategies, bringing different impacts to the competitiveness and internal environment of different organizations. . In this context, the objective of this work is to analyze how strategic choices for the digital transformation of institutions in the Brazilian banking sector have impacted the organizational structure of Brazilian banking institutions in the last ten years and how their adaptation and response has been. An applied research with a qualitative approach was carried out. Regarding the objectives, the research is classified as descriptive and classified as a case study of the phenomenon. The study was carried out between November 2022 and February 2023, when 35 professionals who work or have worked in one of the four largest private financial institutions in the country were interviewed, divided into three groups: 15 banking professionals who do not hold a management position, 15 banking managers, and for these two groups back and front office professionals were selected, as well as 5 sector experts, who hold or have held strategic positions. Significant changes were observed in the organizational structures of Brazilian banks, with the identification of intervening elements, such as the digitalization and automation of processes that led to the review of internal processes and routines, forms of communication (internal and with customers), with a new definition of forms coordination and supervision of activities. The technical system, the size of the institutions and the environment in which they are inserted, led to the reduction of hierarchical levels, the extinction of positions and functions, the creation of different spaces and work environments, in addition to the intensification of the use of technologies that bring people and reduce the information path. Positive results were observed from structural changes, such as improvements to internal processes, increased productivity and more focus on customers, which confirm that the adaptability of the organizational structure helps to sustain competitive advantages. As negative results, even with advances in automation, the downsizing of the hierarchy generated an accumulation of tasks and responsibilities for professionals. From the point of view of work format choices, even if technology supports in-person work and remote work, there is still a culture of managers depending on the direct supervision of employees, which can make changes in the organizational structure difficult. As a theoretical contribution, the present study showed that it is conducive and necessary to bring together different approaches to analyze digital transformation, work formats and adaptive responses of the organizational structure, involving the field of strategy with the elements of organizational design, showing that the capacity structure response and adaptation helps in the microfoundation of resource reconfiguration of dynamic capabilities. As a practical contribution, it is expected to help managers and professionals identify which elements of the organizational structure are required to support strategic choices, such as digital transformation and changes in the work format, in order to adapt them as an adaptive response from the organization. facing the dynamics of its environment.